Engineering Immunomodulatory Biomaterials for Regenerating the Infarcted Myocardium - Bloise, Nora; Rountree, Isobel; Polucha, Collin; Montagna, Giulia; Visai, Livia; Coulombe, Kareen L. K.; Munarin, Fabiola (Frontiers in Bioengineering and Biotechnology, 2020)
Coronary artery disease is a severe ischemic condition characterized by the reduction of blood flow in the arteries of the heart that results in the dysfunction and death of cardiac tissue. Despite research over several decades on how to reduce long-term complications and promote angiogenesis in the infarct, the medical field has yet to define effective treatments for inducing revascularization in the ischemic tissue. With this work, we have developed functional biomaterials for the controlled release of immunomodulatory cytokines to direct immune cell fate for controlling wound healing in the ischemic myocardium. The reparative effects of colony-stimulating factor (CSF-1), and anti-inflammatory interleukins 4/6/13 (IL4/6/13) have been evaluated in vitro and in a predictive in vivo model of ischemia (the skin flap model) to optimize a new immunomodulatory biomaterial that we use for treating infarcted rat hearts. Alginate hydrogels have been produced by internal gelation with calcium carbonate (CaCO3) as carriers for the immunomodulatory cues, and their stability, degradation, rheological properties and release kinetics have been evaluated in vitro. CD14 positive human peripheral blood monocytes treated with the immunomodulatory biomaterials show polarization into pro-healing macrophage phenotypes. Unloaded and CSF-1/IL4 loaded alginate gel formulations have been implanted in skin flap ischemic wounds to test the safety and efficacy of the delivery system in vivo. Faster wound healing is observed with the new therapeutic treatment, compared to the wounds treated with the unloaded controls at day 14. The optimized therapy has been evaluated in a rat model of myocardial infarct (ischemia/reperfusion). Macrophage polarization towards healing and global cardiac function measured with echocardiography and immunohistochemistry at 4 and 15 days demonstrate the therapeutic potential of the proposed immunomodulatory treatment in a clinically relevant infarct model.